Characterization of the traditional fermented fish products bagoong isda (fish paste) and bagoong alamang (shrimp paste) - Hidalgo, Melody Mae C. (2012)
Bagoong isda and bagoong alamang are traditional Philippine salt-fermented food products made from the fermentation of fish and shrimp, respectively. Physicochemical analysis, determination of the aerobic plate count, and preliminary identification of the bacteria present in market samples of bagoong isda and bagoong alamang were done. The pH, salt content, and moisture content of bagoong isda were found to be 5.64, 15.57%, and 51.75%, respectively.. For bagoong alamang, the values were 7.55, 27.04%, and 55.75%, respectively. The aerobic plate count for both bagoong isda and bagoong alamang was 4.28 log of 10 cfu/g. Micrococcus and Staphylococcus species comprised the bacterial flora of bagoong isda. On the other hand, the bacterial flora of bagoong alamang included Streptococcus and Bacillus species.